The problem of interaction between the state and religion in modern China - Beysenov, B.K.; Dosmagambetova, D.Zh.; Igisenova, A.R. (Eurasian Journal of Religious Studies, 2019)
The article examines and in a historical aspect analyzes the situation of religion in China. In China, religious activities such as Taoism, Confucianism, Christianity and Islam, as well as the Chinese Buddhist society, the Chinese Taoist society, the Chinese Catholic community, the Chinese Christian community, the Chinese committee of the patriotic movement of Christians, the Chinese Catholic bishop’s college as a nationwide religious community, are allowed with their attitudes are vested with the right to choose their governing body and leader. There are about 70 religious educational institutions in China, in particular, such as the Nanjing Christian Religious Academy, the Islamic Institute of China, the Tao Institute, the Buddha Institute, the Chinese Catholic Theosophical Academy, etc. Geopolitical changes and globalization processes taking place in the modern world affect the tasks of the state authorities of the PRC in the religious sphere. The purpose of this study is to analyze the Chinese model of religious activity regulation. The article considers the features of politics in the sphere of religion, as well as the religious situation in China. The religious situation in Tibet, Xinjiang Uygur Autonomous Region is shown. The dynamics of religiosity is given, the emphasis is on changing state policy in the field of religion, creating a regulatory framework for the regulation of state-church relations in China. The article used such methods as the unity of historical and logical, concrete historical approach, methods of comparative and system analysis.